Storage ring at HIE-ISOLDE - Grieser, Manfred; Litvinov, Yuri A.; Blaum, Klaus; Artemyev, Anton; Atanasov, Dinko; Fischer, David; Kreim, Susanne; Repnow, Roland; Schwalm, Dirk; Shubina, Daria; Winckler, Nicolas (European physical journal special topics, 2012)
We propose to install a storage ring at an ISOL-type radioactive beam facility for the first time. Specifically, we intend to setup the heavy-ion, low-energy ring TSR at the HIE-ISOLDE facility in CERN, Geneva. Such a facility will provide a capability for experiments with stored secondary beams that is unique in the world. The envisaged physics programme is rich and varied, spanning from investigations of nuclear ground-state properties and reaction studies of astrophysical relevance, to investigations with highly-charged ions and pure isomeric beams. The TSR might also be employed for removal of isobaric contaminants from stored ion beams and for systematic studies within the neutrino beam programme. In addition to experiments performed using beams recirculating within the ring, cooled beams can also be extracted and exploited by external spectrometers for high-precision measurements. The existing TSR, which is presently in operation at the Max-Planck Institute for Nuclear Physics in Heidelberg, is well-suited and can be employed for this purpose. The physics cases as well as technical details of the existing ring facility and of the beam and infrastructure requirements at HIE-ISOLDE are discussed in the present technical design report.